AB1216 Quantitative evaluation of therapeutic changes in digital psoriatic arthritis with contrast enhanced dual energy computed tomography iodine map. (12th June 2018) - Kawakami, R.; Fukuda, T.; Ogiwara, S.; Momose, M.; Tokashiki, T.; Umezawa, Y.; Asahina, A.; Matsushima, M.; Nakagawa, H.; Fukuda, K.
Abstract : Background: Dual Energy Computed Tomography (DECT) iodine map is highly sensitive in depicting the inflammatory changes of psoriatic arthritis (PsA). A modified PsA Magnetic Resonance Imaging Scoring System (mPsAMRIS) was developed to assess the severity of PsA on DECT iodine map 1, 2, 3 . DECT iodine map also enables the calculation of iodine uptake in the lesion, which provides a more direct measure of disease activity 4 . However, the usefulness of DECT in evaluating the therapeutic effect of PsA by using iodine quantification, is still undetermined. Objectives: To assess the validity of DECT iodine map in evaluating the therapeutic effect of PsA by iodine quantification. Methods: The study included symptomatic PsA patients who underwent two consecutive contrast-enhanced DECT of hand or foot, prior and post medical intervention. All images were independently evaluated by two radiologists. Each symptomatic joint and matched non-symptomatic control joint were scored with mPsAMRIS. To measure the iodine uptake, the region of interest was selected at the level where the joint was most affected. The treatment effect of mPsAMRIS and iodine uptake was calculated by subtracting the results of the matched non-symptomatic joints. Results: The demographics and clinical characteristics of enrolled patients are shown below. Inter-reader agreement for mPsAMRIS was moderate or sufficient (weighted κ(w)=0.57 for pre-treatment; weighted κ(w)=0.70 for post-treatment, respectively). Inter-reader agreement for iodine quantification for pre- and post-treatment showed significant correlation (Spearman's ρ=0.93 p<0.005, Spearman's ρ=0.95 p<0.005, respectively). Both mPsAMRIS and iodine uptake showed significant improvement after treatment for both readers (Wilcoxon signed-rank test: z=7.37, z=5.98 for reader 1, z=7.38, z=6.20 for reader 2, p<0.005 for all z). The treatment effect of mPsAMRIS and iodine uptake showed significant correlation (Spearman's ρ=0.56 p<0.005 for reader 1, Spearman's ρ=0.57 p<0.005 for reader 2). Graph shows the correlation between change of mPsAMRIS score and iodine uptake. Conclusions: A significant improvement of inflammatory changes in PsA was confirmed by iodine uptake post-treatment, which was in-keeping with mPsAMRIS, and there was a strong correlation between the mPsAMRIS scoring system and iodine quantification. Therefore, iodine quantification may be useful in evaluating the treatment effect of PsA. Furthermore, changes in iodine uptake were observed even with small changes of mPsAMRIS, thus iodine uptake may provide a more sensitive and detailed measure of inflammatory activity in PsA. References: [1] Ostergaard M, et al. J Rheumatol. 2009, 36:1816–24 [2] Fukuda T, et al. Radiology. 2017, 284:134–142 [3] Fukuda T, et al. Eur Radiol. 2017, 27:5034–5040 [4] Chandarana H, et al. Am J Roentgenol. 2011, 196: W693-W700 Disclosure of Interest: None declared